Energy Hub Gas: A Modular Setup for the Evaluation of Local Flexibility and Renewable Energy Carriers Provision - Rafael Poppenborg; Malte Chlosta; Johannes Ruf; Christian Hotz; Clemens Düpmeier; Thomas Kolb; Veit Hagenmeyer (Energies, 2023)
The ambitious targets for the reduction of Greenhouse Gas (GHG) emissions force the enhanced integration and installation of Renewable Energy Sources (RESs). Furthermore, the increased reliance of multiple sectors on electrical energy additionally challenges the electricity grid with high volatility from the demand side. In order to keep the transmission system operation stable and secure, the present approach adds local flexibility into the distribution system using the modular Energy Hub Gas (EHG) concept. For this concept, two different test cases are configured and evaluated. The two configured EHGs demonstrate the ability to provide flexibility and adaptability by reducing the difference between maximal and minimal load in the surrounding grid infrastructure by <semantics>30%</semantics> in certain time periods. Furthermore, the average energy exchange is reduced by <semantics>8%</semantics>. Therefore, by relieving the grid infrastructure in the local surroundings, the additional potential of RES is enabled and the curtailment of existing ones can be reduced.